OS 04-06 HOW TO CONTROL HIGH BLOOD PRESSURE AFTER CORONARY REVASCULARIZATION IN PATIENTS REFERRED TO IN- HOUSE CARDIAC REHABILITATION? SINGLE CENTER EXPERIENCE. (September 2016) - Burazor, Ivana; Susak, Stamenko
Abstract : Objective: After stent or bypass surgery blood pressure (BP) can go up for multiple reasons among which are: stress and tense of the patient unsure about the future, the pain of the cut and because some of the blood pressure medication, which the patient was receiving preoperatively may get withdrawn post operatively, thereby leading to shooting up the BP. In certain patients, BP actually comes down after surgery and returns back to the pre-operative levels 4 to 6 weeks down the track. We aimed to investigate the incidence of high BP after coronary artery bypass surgery (CABG) in patients referred to our in- house cardiac rehabilitation program. Design and method: Out of 2276 patients admitted for in-hospital cardiac rehabilitation, we studied two hundred ten patients with previous CABG or stent (64% males, aged 65.82 ± 10.01 years). Risk factors and medications were noted. Exercise test were performed on admisson and after 21 days of in-hospital rehabilitationn. Patients were selected for exercises program: free walking, cycle and/or Nyllin steps. BP was measured every morning, before and immediately after the exercise, after a break. Results: High BP was noted in 27% of patients referred to our in house cardiac rehabilitation program with the maximum of 210mmHg for systolic and 110 for diastolic pressure. Most of the patients (86%) were taking preoperative antihypertensive drugs. We optimized the dose in 35% while in 68% ACE inhibitors were change to ARB (irbesartan predominantly) to optimize BP and achieve target levels. None of the patient had severe complicates due to BP arise. All the patients successfully finished in house cardiac rehabilitation program. Conclusions: CABG and stent can help to restore blood flow to an area of the heart. However, they do not stop the progression of atherosclerosis. High blood pressure can be successfully detected and treated during in house supervised cardiac rehabilitation program.